2015
DOI: 10.1002/anie.201503914
|View full text |Cite
|
Sign up to set email alerts
|

Organic Crystals with Near‐Infrared Amplified Spontaneous Emissions Based on 2′‐Hydroxychalcone Derivatives: Subtle Structure Modification but Great Property Change

Abstract: A series of highly efficient deep red to near-infrared (NIR) emissive organic crystals 1-3 based on the structurally simple 2'-hydroxychalcone derivatives were synthesized through a simple one-step condensation reaction. Crystal 1 displays the highest quantum yield (Φf) of 0.32 among the reported organic single crystals with an emission maximum (λem) over 710 nm. Comparison between the bright emissive crystals 1-3 and the nearly nonluminous compounds 4-7 clearly gives evidence that a subtle structure modificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
111
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(119 citation statements)
references
References 48 publications
8
111
0
Order By: Relevance
“…These PMI assemblies, therefore, possess unique optical and electronic properties, such as H-aggregates with strongly red-shifted absorbance bands, suggestive of high mobility charge tranfer exctions. As with other organic crystals, 22,23,32 the electronic properties of these PMI assemblies are highly sensitive to small changes in the packing of chromophores within the nanostructures. 29,33 In our previous work we found that crystalline packing of chromophore amphiphiles based on PMIs can be altered through side-chain modification at the imide 33 or 9-position.…”
Section: Introductionmentioning
confidence: 98%
“…These PMI assemblies, therefore, possess unique optical and electronic properties, such as H-aggregates with strongly red-shifted absorbance bands, suggestive of high mobility charge tranfer exctions. As with other organic crystals, 22,23,32 the electronic properties of these PMI assemblies are highly sensitive to small changes in the packing of chromophores within the nanostructures. 29,33 In our previous work we found that crystalline packing of chromophore amphiphiles based on PMIs can be altered through side-chain modification at the imide 33 or 9-position.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, Tang and co‐workers have demonstrated that the dual‐state emissive fluorophores ought to maintain substantial rigidity with limited intramolecular motions to emit in solution, and simultaneously possess considerable twisting conformations to give aggregation‐induced emission (AIE) in the solid state . 2′‐Hydroxychalcone derivatives with donor–acceptor skeletons can exhibit strong red to near‐infrared (NIR) emissions in the solid state activated by excited‐state intramolecular proton transfer (ESIPT) process upon excitation, whilst they only give a local emission (LE) band at much shorter wavelength in protic solvents . Therefore, 2′‐hydroxychalcone may be among the more easily accessible fluorophores fulfilling the requirement of dual‐state emissions.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas 3MC , 5MC and 6MC all displayed fluorescent enhancement upon incubation with HSA (Supporting Information, Figure S1), 4MC displayed a dramatic emission color change from red to green under identical conditions (Scheme c). The red emission of 4MC in solid/aggregated state can be assigned to the methoxyl group in right position, which leads to the aggregation with edge‐to‐face packing to reduce π–π stacking in the solid state …”
Section: Methodsmentioning
confidence: 99%
“…An illustrative example is a derivative of 2′‐hydroxychalcone (HC), which upon the addition of a methoxy group in para position with respect to the hydroxyl group turns off its emissive character in crystal form, bringing the fluorescence quantum yield from 0.32 to less than 0.01 . The new molecule is (E)‐1‐(2‐hydroxy‐5‐methoxyphenyl)‐3‐(4[dimethylamino]phenyl)prop‐2‐en‐1‐one (DAP).…”
Section: Featuresmentioning
confidence: 99%
“…The optimization of excited state geometries in detailed condensed phase environments has numerous applications. For instance, the fluorescence of HC (see Section 3.1.1) can also be switched off by the substitution of a methyl group in para position with respect to the hydroxyl group, resulting in another dark compound: (2E)‐3‐[4‐(dimethylamino)phenyl]‐1(2‐hydroxy‐5‐methylphenyl)‐2‐propen‐1‐one (DMAP) …”
Section: Featuresmentioning
confidence: 99%